Neo-Sumerian barley allotment rolls from the Umma region - Al-Taee, Ammar M.; Feliu Mateu, Lluís (Publicacions i Edicions de la Universitat de Barcelona, 2024)
This volume focuses on contacts between Anatolian languages within and outside Anatolia. The selected essays, written by members of ongoing research projects on Anatolian languages, present case studies from both the first and second millennia. These include etymological and morphophonological investigations within the framework of Graeco-Anatolian contacts, as well as a critical essay on the possible Anatolian-Etruscan contacts. Alongside strictly linguistic analysis, the essays cover different aspects of cultural contacts (the origin of the word for ‘salt’ in Luwian), toponyms (in Lycia), and religion (the god called King of Kaunos), and are introduced with a detailed overview of the origins of the Anatolian linguistic landscape.